Evaluating the patient-perceived impact of clinical pharmacy services and proactive follow-up care in an ambulatory chemotherapy unit. (June 2017) - Crespo, Andrea; Tyszka, Malgorzata
Purpose: To evaluate the patient-perceived impact of delivery of clinical pharmacy services, including a proactive follow-up program, on patient understanding, satisfaction, and toxicity management. Methods: Patients who had received clinical pharmacy services at their initial chemotherapy treatment were identified and asked to complete a 20-point survey at the second or subsequent treatment. The services that the survey evaluated consist of face-to-face education during the first treatment and proactive telephone follow-up 3 to 7 days later. Results: A total of 107 of the 112 respondents (95.5%) indicated that the time with the pharmacist at the first treatment was worthwhile and 92.6% of respondents reported that the interaction with the pharmacist increased their understanding of the medication regimen. Of the 113 respondents, the majority was either "Very Satisfied" or "Satisfied" with the time the pharmacist spent with them (94.7%), and the pharmacist's ability to answer their questions (92.9%). In addition, survey results indicate that the clinical pharmacy input provided in the pharmacist call-back program is valuable, with 92.6% of the 82 respondents indicating that this service is worthwhile, and 91.4% of 93 respondents stating that the pharmacist input helped them to manage side-effects at home. Conclusions: Survey results indicate that patients value clinical pharmacy services in the ambulatory oncology chemotherapy setting. These services contribute to improve patient understanding of the medication regimen, a high level of patient satisfaction, and self-management of treatment-related toxicities. These results support the provision of clinical pharmacy services and proactive follow-up programs in ambulatory chemotherapy units.